Tendency of exports technology structure and exports concentration in the Balkan economies 2000-2012 - Nikolić, Goran (Industrija, 2013)
At the beginning of the 21st century there was a tendency of mild improvement of the quality of exports of Balkan countries, which can be traced through a slight increase in the share of goods of higher levels of processing (skill-intensive manufactures and medium- and high-tech products). In spite of that, the quality level of exports from Balkan economies lags greatly behind the countries in the EU and to a lesser extent the Central European economies in transition, with some signs of catching-up over time. The stagnant and relatively high levels of Export concentration ratio and low share of high processing goods are indicating that Balkan economies are increasingly specializing in price-sensitive markets.For export success it is of great importance to have the transfer of modern technology and investment, especially FDI, in competitive sectors which would 'spread' export offer. Improved approach to employment policy regulations and an extensive re-organization of science and education system is needed. One of the reasons for Balkan countries’ weak export lies in industrial policy, which would be able to promote innovation, product quality and high technological standards.